PENINGKATAN PENGENALAN KOSA KATA BAHASA INGGRIS PADA ANAK MELALUI PERMAINAN KARTU GAMBAR - Huda, Khairul; Purmadi, Ary; Iman, Nurul (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2018)
The Increasing English Vocabulary Introduction Through Picture Card Games In Children Class B PAUD Nurul Arafah Sembalia Sub-District East Lombok In The academic year 2016/2017 can increase with little direction. The purpose of this research is to know the improvement of vocabulary introduction in child’s English through the picture card game in Class B of PAUD Nurul Arafah of Sembalia Sub-district, East Lombok In The academic year 2016/2017. The results showed an increase in vocabulary in English through a picture card game in children in the class b PAUD nurul arafah sub district with a little direction. The research method used is to use action research class (Action Research) with the subject of research is Class B PAUD Nurul Arafah District Sembalia East Lombok district with the number of subjects 19 children. Technique of collecting data with menggiunakan observation, interview, observation and Sheet In English Through Picture Card Game Image Year 2016/2017. assessment (field notes). the results of research in the first cycle is 53.49% and in the second cycle increased by 77.27% it can be concluded that the increase of the I-II cycle increased on average by 22.12%. %. From result of research that happened Increase of Introduction of Sense Keyword: Increasing English Vocabulary Introduction, Picture Card Games